Attitudes toward anticoagulation for postoperative atrial fibrillation: A nationwide survey of VA providers. Issue 11 (28th October 2020) - Riad, Fady S.; German, Konstantin; Deitz, Sarah; Sahadevan, Jayakumar; Sundaram, Varun; Waldo, Albert L.
Abstract: Introduction: Postoperative atrial fibrillation (POAF) is a common complication after cardiac surgery. Though often felt to be self‐limited, this complication has been associated with increases in both short and long‐term stroke and mortality. Several studies have also shown a high rate of AF recurrence. Optimal treatment strategy is not yet defined, and the role of anticoagulation (AC) is unclear. Our objective was to determine provider attitudes toward management of this common complication. Methods: A survey consisting of 15 multiple choice questions was distributed to providers at Veterans Healthcare Administration hospitals nationwide. Results: The majority of respondents were cardiologists. Practices varied drastically with respect to AC use for patients with POAF who were discharged in normal sinus rhythm. Less variability existed for patients discharged in AF. There was no clear consensus regarding other factors to consider when deciding on AC therapy, including length of episode, or risk factors for stroke such as CHA2 DS2 ‐VASc score. There was also no consensus on duration of therapy or need for post discharge cardiac monitoring. Conclusion: Our data indicate a wide variability in the management of POAF. This reflects conflicting recommendations in the guidelines, as well as a paucity of prospective treatment trials in this field. Nevertheless, a growing evidence base suggests that this complication carries potentially serious long‐term morbidity and mortality, and better evidence for its management is needed.